2018
DOI: 10.1016/j.spinee.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Bony ingrowth potential of 3D-printed porous titanium alloy: a direct comparison of interbody cage materials in an in vivo ovine lumbar fusion model

Abstract: A direct comparison of interbody implants demonstrates significant and measurable differences in biomechanical, µ-CT, and histologic performance in an ovine model. The 3D-printed porous titanium interbody cage resulted in statistically significant reductions in ROM, increases in the bone ingrowth profile, as well as average construct stiffness compared with PEEK and PSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
154
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 38 publications
2
154
2
Order By: Relevance
“…We observed that osteointegration with such small gaps was achieved at segments containing the mesh structure but not at those not containing the mesh structure. A few animal studies have previously focused on the osteointegration of a 3D-printed titanium implant [11,12,15,20,21,27], and three of these specifically focused on using vertebral cages for flat bones [12,15,20]. However, it is difficult to compare the results of these studies with those of the present study, which used the long tubular bone.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…We observed that osteointegration with such small gaps was achieved at segments containing the mesh structure but not at those not containing the mesh structure. A few animal studies have previously focused on the osteointegration of a 3D-printed titanium implant [11,12,15,20,21,27], and three of these specifically focused on using vertebral cages for flat bones [12,15,20]. However, it is difficult to compare the results of these studies with those of the present study, which used the long tubular bone.…”
Section: Discussionmentioning
confidence: 89%
“…Because 3D printing is an additive manufacturing technique, the porosity and roughness of a surface can be appropriately adjusted using this technique. Previous studies have reported that a titanium alloy implant with appropriate porosity or roughness can enhance tissue integration [11,12,15,[17][18][19][20][21]. However, to our knowledge, this potential has not yet been evaluated in a clinical application in humans.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Whilst an ideal pore structure has yet to be evidenced, in vivo research has demonstrated improved osseointegration of porous metallic implants compared to conventional materials. Multiple studies of porous Ti lumbar fusion cages in an ovine model have demonstrated significantly higher osseointegration than both conventional polymer, and titanium coated polymer alternatives [90,91]. Several manufacturers now utilise AM in the production of spinal fusion implants, as identified in Table 1, both in Ti and CoCr based alloys.…”
Section: Mesoscale Design For Osseointegrationmentioning
confidence: 99%